Virtualization From the Desktop to the Enterprise - Wolf, Chris; Halter, Erick M.; SpringerLink (Online service) (Berkeley, CA : Apress, 2005)
Creating a virtual network allows you to maximize the use of your servers. Virtualization: From the Desktop to the Enterprise is the first book of its kind to demonstrate how to manage all aspects of virtualization across an enterprise. (Other books focus only on singular aspects of virtualization, without delving into the interrelationships of the technologies.) This book promises to cover all aspects of virtualization, including virtual machines, virtual file systems, virtual storage solutions, and clustering, enabling you to understand which technologies are right for your particular environment. Furthermore, the book covers both Microsoft and Linux environments.
Examining the Anatomy of a Virtual Machine -- Preparing a Virtual Machine Host -- Installing VM Applications on Desktops -- Deploying and Managing VMs on the Desktop -- Installing and Deploying VMs on Enterprise Servers -- Deploying and Managing Production VMs on Enterprise Servers -- Backing Up and Recovering Virtual Machines -- Using Virtual File Systems -- Implementing Failover Clusters -- Creating Load-Balanced Clusters -- Building Virtual Machine Clusters -- Introducing Storage Networking -- Virtualizing Storage -- Putting It All Together: The Virtualized Information System.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books